Operational Planning: The Integration Of Programming and Budgeting - Camillus, John C.; Grant, John H. (Academy of Management Review, 1980)
Two distinct and sequential processes of programming and budgeting are recommended in the current literature and have been widely adopted in practice as means for translating corporate strategy into action plans and financial statements. We suggest that this distinction results from debatable interpretations of a seminal conceptual framework of planning and control, and represents inefficient and less effective practice compared to our proposed alternative.